Securing a SaaS application on AWS Cloud - Siddhartha Sourav Panda; Nishanth Pathi; Shinu Abhi (International Journal of Computer and Information System (IJCIS), 2023)
The last few years have seen tremendous growth in cloud adoption especially the new age companies and startups in multiple domains are embracing cloud technologies to avoid on-premises costs of maintaining the systems. As organizations grow and continue to invest in digital transformation, the cloud is becoming an ever more crucial part of the organization. For startups, it is highly required that they look at their cloud security components and make them robust to avoid a cyber-attack and reputation damage. Year after year IT world has been witnessing multiple series of news headlines and data leaks that occurred because of cloud architecture misconfigurations. In this article, the authors will explore Amazon Web Services (AWS), which is one of the top cloud service providers in the world. This paper target is to educate and set up a guideline for a secured architecture baseline on AWS cloud adoption for new or existing customers to review their architecture and encourage them to deploy the security components on AWS. This paper provides a brief overview of the various architectures proposed and implemented that can act as a solution for handling the various issues related to Cloud Computing, especially Cloud Security.